2001
DOI: 10.1152/ajpheart.2001.280.6.h2726
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte apoptosis and ventricular remodeling after myocardial infarction in rats

Abstract: We investigated the role of cardiomyocyte apoptosis in the remodeling of the left ventricle from 24 h to 12 wk after myocardial infarction in the rat. Infarct size planimetry, quantification of cardiomyocyte apoptosis, terminal deoxynucleotide transferase-mediated dUTP nick-end labeling (TUNEL) methodology, and echocardiography (left ventricular diastolic diameter and ejection fraction) were performed. Sham-operated animals showed low rates of cardiomyocyte apoptosis (0.03%) and no change in diastolic diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
182
1
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 270 publications
(207 citation statements)
references
References 29 publications
17
182
1
7
Order By: Relevance
“…More specifically, RG significantly preserved LVEDD and LVESD increased almost from 7 days post‐MI in our study. This observation provides a possible association towards apoptosis in the RR which has previously been associated with post‐infarction LVR, cardiac dilation, and increased cardiac fibrosis after MI, respectively 37. In addition, we also observed a shift of the Bcl2/Bax ratio toward the regulator protein Bcl2 in the RR (although not statistically significant).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…More specifically, RG significantly preserved LVEDD and LVESD increased almost from 7 days post‐MI in our study. This observation provides a possible association towards apoptosis in the RR which has previously been associated with post‐infarction LVR, cardiac dilation, and increased cardiac fibrosis after MI, respectively 37. In addition, we also observed a shift of the Bcl2/Bax ratio toward the regulator protein Bcl2 in the RR (although not statistically significant).…”
Section: Discussionsupporting
confidence: 71%
“…It has been shown that in contrast to the BZ, the amount of apoptosis in the RR is correlated with an increase in the ventricular diameter 4 weeks after infarction 37. More specifically, RG significantly preserved LVEDD and LVESD increased almost from 7 days post‐MI in our study.…”
Section: Discussionsupporting
confidence: 49%
“…Four weeks after the STZ or citrate buffer injections the animals underwent either sham or MI operation (n=7-11 in each group). MI was produced by ligation of the left anterior descending coronary artery as described [3]. The rats were killed 1, 4 and 12 weeks after the operation, the hearts were weighed, embedded in paraffin, and cut into sections for histology, planimetry, and assessment of apoptosis and connective tissue growth factor (CTGF).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of signs of acute MI (eosinophilia, karyolysis, and leucocyte infiltration) or collagen scars compatible with MI was verified by examination of Van Gieson stained transverse left ventricular (LV) sections. Infarct size was determined planimetrically [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation